2014
DOI: 10.12659/ajcr.890661
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Hepatocellular Carcinoma to Parotid Glands

Abstract: Patient: Male, 66Final Diagnosis: Hepatocellular carcinomaSymptoms: Abdominal distension • painful right facial swelling • weight lossMedication: —Clinical Procedure: —Specialty: —Objective:Rare diseaseBackground:Hepatocellular carcinoma is a common cancer, but it rarely metastasizes to the salivary glands. A review of the literature revealed only 5 reported cases of hepatocellular carcinoma metastatic to parotid glands. We here report an additional case of this rare association.Case Report:A 66-year-old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Previous studies have revealed many factors contributing to HCC pathogenesis, such as hepatitis B/C virus infection, alcohol abuse, liver cirrhosis, gene mutation, and so on [3]. Despite great advances in HCC treatment strategies such as sorafenib, liver transplantation and percutaneous ablation, the survival rate of HCC patients remains very poor, 3-5% within 5 years [3][4][5][6][7]. With the development of bioinformatics, gene expression profile of HCC has been fully characterized and many of the genetic abnormalities contributing to HCC, such as potential oncogenes and tumor suppressor genes, are well known [8][9][10].…”
mentioning
confidence: 99%
“…Previous studies have revealed many factors contributing to HCC pathogenesis, such as hepatitis B/C virus infection, alcohol abuse, liver cirrhosis, gene mutation, and so on [3]. Despite great advances in HCC treatment strategies such as sorafenib, liver transplantation and percutaneous ablation, the survival rate of HCC patients remains very poor, 3-5% within 5 years [3][4][5][6][7]. With the development of bioinformatics, gene expression profile of HCC has been fully characterized and many of the genetic abnormalities contributing to HCC, such as potential oncogenes and tumor suppressor genes, are well known [8][9][10].…”
mentioning
confidence: 99%
“…The prognosis of HCC is poor and most patients are generally diagnosed at advanced stage [2,3]. Approximately 600,000 HCC patients die annually, making it the fifth most common cause of cancer-related death worldwide [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide, with very high morbidity and mortality [ 1 ]. The prognosis of HCC is poor and most patients are generally diagnosed at advanced stage [ 2 , 3 ]. Approximately 600,000 HCC patients die annually, making it the fifth most common cause of cancer-related death worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%